EFL Students’ Acceptance of AI Tools in English Writing: A Technology Acceptance Model Perspective : A Technology Acceptance Model Perspective - Resti Paulijah; Siswana Siswana (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The increasing use of Artificial Intelligence (AI) tools has influenced various aspects of education, including English writing. This study aimed to investigate EFL students’ acceptance of AI tools in English writing using the Technology Acceptance Model (TAM). A quantitative survey design was employed, involving 151 EFL university students from several universities in Jakarta who had experience using AI tools such as ChatGPT, Gemini, and Grammarly in writing activities. Data were collected through an online questionnaire consisting of four TAM dimensions: Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using AI Tools, and Behavioral Intention. The questionnaire demonstrated satisfactory reliability, with Cronbach’s Alpha values ranging from 0.806 to 0.881. The data were analyzed using descriptive statistics. The findings revealed a high level of acceptance of AI tools across all dimensions. Behavioral Intention showed the highest mean score (M = 20.85), followed by Attitude Toward Using AI Tools (M = 20.83), Perceived Ease of Use (M = 20.70), and Perceived Usefulness (M = 20.26). The results indicate that students perceived AI tools as useful, easy to use, and beneficial in supporting various stages of the writing process. Overall, the study suggests that AI tools have been positively accepted by EFL students and may serve as valuable resources for enhancing English writing activities in higher education contexts.